The same stuff as stars - Paterson, Katherine (Houghton Mifflin Harcourt, 2016)
When Angel's self-absorbed mother leaves her and her younger brother with their poor great-grandmother, the eleven-year-old girl worries not only about her mother and brother, her imprisoned father, the frail old woman, but also about a mysterious man who begins sharing with her the wonder of the stars.